Facile Assembly of Thermosensitive Liposomes for Active Targeting Imaging and Synergetic Chemo-/Magnetic Hyperthermia Therapy - An, Yanli; Yang, Rui; Wang, Xihui; Han, Yong; Jia, Gang; Hu, Chunmei; Zhang, Zhiyuan; Liu, Dongfang; Tang, Qiusha (Frontiers in Bioengineering and Biotechnology, 2021)
Cancer stem cells are thought to be responsible for the recurrence of liver cancer, highlighting the urgent need for the development of effective treatment regimens. In this study, 17-allylamino-17-demethoxygeldanamycin (17-AAG) and Fe3O4-loaded thermosensitive liposomes (TSLs) conjugated to anti-CD90 (CD90@17-AAG/TMs) were developed for temperature-responsive CD90-targeted synergetic chemo- /magnetic hyperthermia therapy and simultaneous imaging in vivo. The targeting ability of CD90@Dir/TMs was studied with near-infrared resonance imaging and magnetic resonance imaging and the anti-tumor effect of CD90@17-AAG/TMs-mediated magnetic thermotherapy was evaluated in vivo. After treatment, the tumors were analyzed with western blotting, hematoxylin and eosin staining, and immunohistochemical staining. The relative intensity of fluorescence was approximately two-fold higher in the targeted group than in the non-targeted group, while the T2 relaxation time was significantly lower in the targeted group than in the non-targeted group. The combined treatment of chemotherapy, thermotherapy, and targeting therapy exhibited the most significant antitumor effect as compared to any of the treatments alone. The anti-CD90 mAb-targeted delivery system, CD90@17- AAG/TMs, exhibited powerful targeting and antitumor efficacies against CD90+ liver cancer stem cells in vivo.